2006
DOI: 10.1097/01.aids.0000200535.02232.1b
|View full text |Cite
|
Sign up to set email alerts
|

Enfurvitide prevents vertical transmission of multidrug-resistant HIV-1 in pregnancy but does not cross the placenta

Abstract: The use of previously successful antiretroviral regimens in mother-to-child transmission (MTCT) prevention will be increasingly challenged by the rising prevalence of multidrug-resistant (MDR) HIV. We used enfurvitide together with an optimized antiretroviral backbone to prevent the MTCT prevention of MDR HIV in two pregnant women. The measurement of maternal and foetal peripheral blood levels of enfurvitide showed no evidence of transplacental transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 7 publications
1
10
0
3
Order By: Relevance
“…Enfurvitide, a 36-amino acid peptide also known as Fuzeon works by inhibiting the structural rearrangement of HIV-1 gp41 to block the fusion of HIV-1 virions with their target cell membrane. Brennan-Benson et al showed that Fuzeon prevents vertical transmission of HIV-1 in pregnancy, but does not cross the placenta [55]. We have shown that some peptides are effective at preventing HCMV infection.…”
Section: Discussionmentioning
confidence: 56%
“…Enfurvitide, a 36-amino acid peptide also known as Fuzeon works by inhibiting the structural rearrangement of HIV-1 gp41 to block the fusion of HIV-1 virions with their target cell membrane. Brennan-Benson et al showed that Fuzeon prevents vertical transmission of HIV-1 in pregnancy, but does not cross the placenta [55]. We have shown that some peptides are effective at preventing HCMV infection.…”
Section: Discussionmentioning
confidence: 56%
“…L'étude de la littérature retrouve, outre nos sept cas, six cas publiés [9][10][11][12]17] et 12 cas présentés [13] (Tableau 2).…”
Section: Discussionunclassified
“…Even though several authors describe the use of enfuvirtide in pregnancy, 6,7 cord blood testing has never been reported. Enfuvirtide was not detected in the peripheral blood of two neonates whose mothers had adequate blood levels at delivery.…”
Section: Casementioning
confidence: 99%